2023
DOI: 10.1002/ep.14081
|View full text |Cite
|
Sign up to set email alerts
|

Effect of organic loading on bioelectricity generation potential of dual‐chambered microbial fuel cell treating chocolaterie wastewater

Abstract: Microbial fuel cells (MFC) are recent advancements in treating wastewater and generating power simultaneously. In the present study, chocolaterie wastewater rich in organic content was the substrate in a dual‐chambered MFC. Activated Carbon Fiber Felt (ACFF) electrodes (anode and cathode) were separated by Nafion 117 proton exchange membrane in the dual‐chambered reactor. The primary goal was to investigate the impact of organic loading on MFC efficiency in treating chocolaterie wastewater and carrying out mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Recently developed pilot-scale MFCs have demonstrated good performance in terms of long-term stability and sustainability, and a series of effective strategies have been identified to support the operation of MFCs. In the reported cases, most MFCs have been operated for more than a year and have shown relatively stable performance (Table 2), and many studies have reported on the stability and performance response of MFC devices to parameter changes over long periods of operation, including seasonal shifts, 44 water quality fluctuations, 131 temperature variations, 132 pH value swings, 133,134 and load changes. 80,135 In addition, numerous strategies have also been developed to improve efficiency and stability during long-term operation.…”
Section: Cost Efficiency and Stability Of Pilot-scale Mfcsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently developed pilot-scale MFCs have demonstrated good performance in terms of long-term stability and sustainability, and a series of effective strategies have been identified to support the operation of MFCs. In the reported cases, most MFCs have been operated for more than a year and have shown relatively stable performance (Table 2), and many studies have reported on the stability and performance response of MFC devices to parameter changes over long periods of operation, including seasonal shifts, 44 water quality fluctuations, 131 temperature variations, 132 pH value swings, 133,134 and load changes. 80,135 In addition, numerous strategies have also been developed to improve efficiency and stability during long-term operation.…”
Section: Cost Efficiency and Stability Of Pilot-scale Mfcsmentioning
confidence: 99%
“…Recently developed pilot-scale MFCs have demonstrated good performance in terms of long-term stability and sustainability, and a series of effective strategies have been identified to support the operation of MFCs. In the reported cases, most MFCs have been operated for more than a year and have shown relatively stable performance (Table ), and many studies have reported on the stability and performance response of MFC devices to parameter changes over long periods of operation, including seasonal shifts, water quality fluctuations, temperature variations, pH value swings, , and load changes. , In addition, numerous strategies have also been developed to improve efficiency and stability during long-term operation. For example, a variety of strategies, such as antimicrobial component modification, electrode structural modulation, and in situ artificial removal, were used to eliminate biofouling for cathode sustainability. The maximum power point tracking system, serial or parallel connection, and dc–dc booster circuit are designed to achieve a high energy conversion efficiency .…”
Section: Comparison Of Mfcs With Conventional Wastewater Treatment De...mentioning
confidence: 99%